Drugs of Abuse and their Detection Methodologies: Contribution of Chemical Sensor - K. Jha, Sunil; Hayashi, Kenshi; Yadava, R.D.S. (Current Organic Chemistry, 2015)
Drug of abuse or illicit drugs have become a serious health issue and global evils during the last few decades. Their detection is a significant area of research, for preventing illegal traffic and toxic effects on human health and society. Numerous analytical methods, based on diverse principles, have been developed for the detection of drugs of abuse. The core intention of present review is to pioneer the reader with the varieties of drugs of abuses (availability, formation, and use and ill-use) as well detection techniques developed and employed in the past few years. The study includes a comparative review of analytical detection techniques. Effectiveness of chemical sensors over other analytical techniques is particularly emphasized.
Keywords: verities of illicit drugs